Stumbling giants : transforming Canada's banks for the information age - Meredith, Patricia, 1955-; Darroch, James L. (James Lionel), 1951- (University of Toronto Press, 2017)
In Stumbling Giants, Patricia Meredith and James L. Darroch embark on an audacious and startling examination of Canada's big banks. Meredith and Darroch's new vision for the Canadian banking industry is a call to action for all interested stakeholders to work together in creating a banking system for the twenty-first century.